2016
DOI: 10.1016/j.bbamcr.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Agent, Di-2-Pyridylketone 4,4-Dimethyl-3-Thiosemicarbazone (Dp44mT), Up-Regulates the AMPK-Dependent Energy Homeostasis Pathway in Cancer Cells

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a cellular energy sensor that monitors ATP levels. There is also evidence that AMPK has onco-suppressive properties. Iron plays a crucial role in cellular energy transducing pathways and tumor cell proliferation. Therefore, metals (e.g., iron) could play an important role in the regulation of AMPK-dependent pathways. Hence, this investigation examined the effect of the iron and copper chelator and potent anti-cancer agent, di-2-pyridylketone 4,4-dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 82 publications
6
33
1
Order By: Relevance
“…It has been shown that di-2-pyridylketone 4,4-dimethyl-3-thiose-micarbazone (Dp44mT), a novel iron and copper chelator that has been shown to have anti-cancer activity, increases AMPK activity in various cancer cell lines [52]. This is in contrast to the results of the present study where we have shown activation of AMPK in response to an increase in intracellular iron (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It has been shown that di-2-pyridylketone 4,4-dimethyl-3-thiose-micarbazone (Dp44mT), a novel iron and copper chelator that has been shown to have anti-cancer activity, increases AMPK activity in various cancer cell lines [52]. This is in contrast to the results of the present study where we have shown activation of AMPK in response to an increase in intracellular iron (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Chelation of iron and copper by Dp44mT can therefore inhibit oxidative phosphorylation resulting in accumulation of AMP, which is a potent activator of AMPK [21]. Dp44mT is also known to generate ROS and induce oxidative stress in cells [52]; oxidative stress is known to activate AMPK [21].…”
Section: Discussionmentioning
confidence: 99%
“…D [KLAKLAK] 2 is capable of disrupting mitochondrial membranes, thus leading to apoptosis of cancer cells [ 6 ]. We have chosen a derivative of the iron-chelator Dp44mT [ 9 , 10 , 11 , 12 , 13 ] as a small molecule drug, because it is known to target several pathways in tumors. PLFAERL is cleaved by calpains, Ca 2+ -dependent cytosolic proteases that are overexpressed in virtually all solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is an important element for multiple cellular processes, as for instance proliferation, and DNA synthesis [ 20 , 21 ]. Dp44mT (Di-2-pyridylketone-4, 4, -dimethyl-3-thiosemicarbazone) is known to effectively chelate iron(II) and iron(III), generate reactive radicals[ 10 ], and interact with several pathways: (1) Dp44mT regulates the AMPK-dependent energy homeostasis pathway in cancer cells [ 11 ]; (2) Dp44mT induces endoplasmic reticulum (ER) stress and activates PERK/eIF3α, IRE1α, ATF6, and calmodulin kinase, resulting in ER-stress-associated pro-apoptotic signaling [ 12 ]; (3) Dp44mT decreases the efficacy of mitochondrial peroxidases, such as peroxiredoxin-3 (Prx3), which are important for cell survival in multiple tumors; (4) Dp44mT can selectively inhibit topoisomerase II α in (breast) cancer cells, leading to G 1 cell cycle arrest at nanomolar concentrations [ 9 ]. The dopamine-tethered Dp44mT-derivative is released from the surface of Fe/Fe 3 O 4 nanocarriers, because the dopamine-anchors are replaced by glutathione and other thiol-containing peptides and proteins in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation